2016
DOI: 10.3382/ps/pew136
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation identification and analysis of the chicken genome using a 60K SNP BeadChip

Abstract: Copy number variation (CNV) is an important source of genetic variation in organisms and a main factor that affects phenotypic variation. A comprehensive study of chicken CNV can provide valuable information on genetic diversity and facilitate future analyses of associations between CNV and economically important traits in chickens. In the present study, an F2 full-sib chicken population (554 individuals), established from a cross between Xinghua and White Recessive Rock chickens, was used to explore CNV in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…For example, Xu et al () revealed new genetic variations underlying milk production traits in Holsteins, and Wang, Xu, et al ()) detected several candidate CNVs that may contribute to genetic variations of meat quality traits in pigs. Rao et al () also found a CNVR associated with chicken growth traits. In our study, we first conducted preliminary work regarding the association between CNVRs and reproductive traits.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Xu et al () revealed new genetic variations underlying milk production traits in Holsteins, and Wang, Xu, et al ()) detected several candidate CNVs that may contribute to genetic variations of meat quality traits in pigs. Rao et al () also found a CNVR associated with chicken growth traits. In our study, we first conducted preliminary work regarding the association between CNVRs and reproductive traits.…”
Section: Discussionmentioning
confidence: 92%
“…CNVs that encompass coding regions have the potential to alter gene expression [24], with a concomitant impact on phenotypic traits. Multiple studies have already identified CNVs in diverse chicken breeds [8,11,16,25,26]. Here we aimed to compare CNVs across our three lines to identify loci with the potential to contribute to phenotypic changes in commercial broilers.…”
Section: Genome Sequencing Reveals the Modern Broiler To Be Closely Rmentioning
confidence: 99%
“…CNVs that encompass coding regions have the potential to alter gene expression [22], with a concomitant impact on phenotypic traits. Multiple studies have already identified CNVs in diverse chicken breeds [8,11,16,[23][24][25]. Here we aimed to compare CNVs across our three lines to identify loci with the potential to contribute to phenotypic changes in commercial broilers.…”
Section: Genome Sequencing Reveals the Modern Broiler To Be Closely Rmentioning
confidence: 99%